PENGEMBANGAN LKS GAMSTER (GAMBAR POSTER) MATERI SIFAT-SIFAT BANGUN RUANG PADA SISWA KELAS V SDN BLURU KIDUL 2 SIDOARJO - Hardianti, Rani Dewi; Dewi, Galuh Kartika; Andjariani, Endang Wahju (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Learning is an activity carried out by students and teachers to achieve certain goals. Learning using Gamster has strengths that can be easily understood because posters highlight the power of messages, visuals and colors. The Gamster LKS contains programmed activities that are directly equipped with pictures of how to work so that they are able-to give the impression of being easy and interesting for students. The purpose of thisSstudywwas to determine theodevelopment of the Gamster LKS (Poster Image) material on the properties of spatial structures in fifth grade students at SDN Bluru Kidul 2 Sidoarjo. This research method usesSResearch and Development (R&D). The research steps were developed using the R&D method from the opinion of Sugiyono, 2009. The data analysis0technique used descriptiveEpercentage, normality test, homogeneity test, gain test. The results of this study indicate that the Gamster LKS is feasible to be tested from each validator, it can beeseen from the percentage of assessments that show >80%. The results of the calculation using the gain test with an average pretest value of 54.50 posttest 86.38 and an average value of 0.70 gain test with moderate criteria indicating an increase in the averageAstudent learning outcomes. Student responses were obtained based on studentAassessments of learning activities using LKS by showing the percentage value of students between 97% with very positive criteria.Gamster can provide opportunities for students to explore their learning experiences by giving students the freedom to build their own knowledge related to the surrounding life that relates the material to the events of students' daily lives. Based on the resultsSof this study, itTcan be concludeddthat the Gamster LKS is very much in demand by students.